2007
DOI: 10.1002/rmv.530
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of putative human bornavirus sequences fails to provide evidence implicating Borna disease virus in mental illness

Abstract: All Borna disease virus (BDV) sequences derived from human specimens published till date were thoroughly analysed and compared to sequences of BDV laboratory strains and to BDV sequences from animals which succumbed to classical Borna disease (BD). Despite high sequence conservation of the BDV genome, animal-derived BDV sequences clustered according to their geographic origin. However, in marked contrast, human-derived BDV sequences did not cluster according to their geographic origin but showed high sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 59 publications
3
58
0
Order By: Relevance
“…If local virus reservoirs existed, birds from distinct regions should carry viruses with distinct signatures. The latter scenario may apply for classical BDV, where farm animals seem to get the virus from persistently infected rodents or insectivores (7,8,16,27). Second, in our study we observed that viruses 7308 and 7225, which originated from two partner birds that lived in the same household, were almost identical.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…If local virus reservoirs existed, birds from distinct regions should carry viruses with distinct signatures. The latter scenario may apply for classical BDV, where farm animals seem to get the virus from persistently infected rodents or insectivores (7,8,16,27). Second, in our study we observed that viruses 7308 and 7225, which originated from two partner birds that lived in the same household, were almost identical.…”
Section: Discussionmentioning
confidence: 49%
“…BDV is the causative agent of a progressive neurological disorder that primarily affects horses, sheep, and some other farm animals in central Europe (7,8,20,21,27,29). BDV exhibits a high tropism for the central nervous system in natural and experimental hosts where it can establish persistent, noncytolytic infections of neurons and astrocytes (3,5,10,15,30).…”
mentioning
confidence: 99%
“…Wild rodents such as shrews have been suggested to act as a potential reservoir species responsible for accidental infections of other species (4). Although it has also been suggested that BDV may infect humans and might be associated with certain neuropsychiatric disorders (2), this idea is highly controversial (5). Nonetheless, experimental infection with BDV serves as an important model system for the investigation of viral persistence in the central nervous system and its associated disorders (1,2,6).…”
mentioning
confidence: 99%
“…Another study also reported the association between BDV and encephalitis (through diagnostic methods of WB and RT-PCR [reverse transcription polymerase chain reaction]), yet there was no association with other neurological disorders and controls (14). However, one metaanalysis study did not confirm the association between human BDV infections and psychiatric diseases (15). In addition, Indirect Immunofluorescence Antibody (IFA) and rRT-PCR tests rejected the possible role of BDV in patients with psychiatric diseases (16).…”
Section: Contextmentioning
confidence: 99%